Gibberellin Metabolism in Flowering Plants: An Update and Perspectives - He, Juan; Xin, Peiyong; Ma, Xueting; Chu, Jinfang; Wang, Guodong (Frontiers in Plant Science, 2020)
In plants, gibberellins (GAs) play important roles in regulating plant growth and development. Early studies revealed the large chemo-diversity of gibberellins in plants, while only GA1, GA3, GA4, and GA7 possess biological activity controlling plant development. However, the elucidation of GA metabolic network at molecular level is far lagged behind the chemical discovery of GAs. Recent advances in the downstream of GA biosynthesis (after GA12 formation) suggested that species-specific gibberellin modification acquired during flowering plant evolution. Here we summarize current knowledge of GA metabolism in flowering plants, and the physiological functions of GA deactivation, with a focus on GA 13-hydroxylation. The potential applications of GA synthetic biology for plant developments are also discussed.